Nutrient and food intakes in early life and risk of childhood fractures: a systematic review and meta-analysis. Issue 5 (7th October 2015) - Händel, Mina N; Heitmann, Berit L; Abrahamsen, Bo
ABSTRACT: Background: The identification of detrimental dietary patterns early in life may contribute to reducing the high incidence of fracture among healthy children. However, information based on a systematic review of the effect of various dietary foods and nutrients on fracture risk is lacking. Objective: We conducted a systematic review and meta-analysis of observational studies that examined the association between dietary intake or serum nutritional concentrations and childhood fractures. Design: Studies published up until June 2015 were identified on the basis of a literature search in Medline, Web of Science, and Scopus databases and by hand searching references by first author based on predefined inclusion criteria. A meta-analysis was carried out for case-control studies that examined differences in mean calcium intake in the case compared with the control group. Random-effects analysis was performed on the basis of the effect estimates derived as the differences in mean calcium intakes between cases and controls. Results: From a total of 1960 articles, we identified 18 observational studies, which were primarily case-control in design. Randomized controlled trials were absent, potentially because of unethical aspects related to the enrollment of children randomly assigned to certain dietary exposures and later fracture rates. Overall, fracture risk seemed to be associated with milk avoidance, high energy intake, high cheese intake, high intake of sugar-sweetened beverages, and no breastfeeding. The pooled effect size of the 9 case-control studies that examined mean calcium intake, which had appropriate data for the meta-analysis, showed no association ( P = 0.99) with fair heterogeneity ( I 2 = 69.3%, P = 0.001) with the use of the random-effects model. Conclusions: On the basis of a systematic review of studies that were judged to be of high or medium quality, there is an indication that some nutritional factors seem to be associated with an increased fracture risk among children. The results may be inflated by selection bias, bias in diet reporting, or residual confounding. More high-quality longitudinal observational or intervention studies are needed on the subject.